# 0-1-3-3x-1-5-dx-

Question Number 65593 by Rio Michael last updated on 31/Jul/19
$$\int_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{3}}} \left(\mathrm{3}{x}\:+\:\mathrm{1}\right)^{\mathrm{5}} {dx}\:= \\$$
Commented by mathmax by abdo last updated on 31/Jul/19
$${let}\:{I}\:=\int_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{3}}} \left(\mathrm{3}{x}+\mathrm{1}\right)^{\mathrm{5}} \:\:{changement}\:\:\mathrm{3}{x}+\mathrm{1}\:={t}\:{give} \\$$$${I}\:=\int_{\mathrm{1}} ^{\mathrm{2}} {t}^{\mathrm{5}} \:\frac{{dt}}{\mathrm{3}}\:=\frac{\mathrm{1}}{\mathrm{3}}\left[\frac{{t}^{\mathrm{6}} }{\mathrm{6}}\right]_{\mathrm{1}} ^{\mathrm{2}} \:=\frac{\mathrm{1}}{\mathrm{3}}\left\{\frac{\mathrm{2}^{\mathrm{6}} }{\mathrm{6}}−\frac{\mathrm{1}}{\mathrm{6}}\right\}\:=\frac{\mathrm{2}^{\mathrm{6}} }{\mathrm{3}×\mathrm{6}}−\frac{\mathrm{1}}{\mathrm{18}}\:=\frac{\mathrm{2}^{\mathrm{5}} }{\mathrm{9}}−\frac{\mathrm{1}}{\mathrm{18}}\:=… \\$$
Commented by Rio Michael last updated on 31/Jul/19
$${thanks} \\$$
Commented by Rio Michael last updated on 31/Jul/19
$${why}\:{from}\:\mathrm{1}\:{to}\:\mathrm{2}?\:{limis}? \\$$
Commented by mathmax by abdo last updated on 01/Aug/19
$${i}\:{have}\:{used}\:{the}\:{chang}.\mathrm{3}{x}+\mathrm{1}={t}\:\:{so}\:{x}=\mathrm{0}\:\rightarrow{t}=\mathrm{3}.\mathrm{0}+\mathrm{1}=\mathrm{1} \\$$$${x}=\frac{\mathrm{1}}{\mathrm{3}}\rightarrow{t}=\mathrm{3}.\frac{\mathrm{1}}{\mathrm{3}}+\mathrm{1}\:=\mathrm{2} \\$$
Commented by Rio Michael last updated on 01/Aug/19
$${thank}\:{you}\:{sir} \\$$
Answered by AnjanDey last updated on 31/Jul/19
$$\mathrm{Let},\mathrm{3}{x}+\mathrm{1}=\mathrm{z}\: \\$$$$\:\:\:\:\:\mathrm{or},\mathrm{3}{dx}={d}\mathrm{z} \\$$$$\:\:\:\:\:\mathrm{or},{dx}=\frac{{d}\mathrm{z}}{\mathrm{3}} \\$$$$\therefore\int_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{3}}} \mathrm{z}^{\mathrm{5}} \centerdot\frac{{d}\mathrm{z}}{\mathrm{3}} \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{3}}\int_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{3}}} \mathrm{z}^{\mathrm{5}} \:{d}\mathrm{z} \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{3}}\left[\frac{\mathrm{z}^{\mathrm{6}} }{\mathrm{6}}\right]_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{3}}} \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{3}}\left[\frac{\left(\mathrm{3}{x}+\mathrm{1}\right)^{\mathrm{6}} }{\mathrm{6}}\right]_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{3}}} \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{3}}×\frac{\mathrm{1}}{\mathrm{6}}\left[\left(\mathrm{3}{x}+\mathrm{1}\right)^{\mathrm{6}} \right]_{\mathrm{0}} ^{\frac{\mathrm{1}}{\mathrm{3}}} \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{18}}\left[\left(\mathrm{3}×\frac{\mathrm{1}}{\mathrm{3}}+\mathrm{1}\right)^{\mathrm{6}} −\left(\mathrm{3}×\mathrm{0}+\mathrm{1}\right)^{\mathrm{6}} \right] \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{18}}\left[\mathrm{2}^{\mathrm{6}} −\mathrm{1}^{\mathrm{6}} \right] \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{18}}\left[\mathrm{64}−\mathrm{1}\right] \\$$$$\:\:=\frac{\mathrm{1}}{\mathrm{18}}×\mathrm{63} \\$$$$\:\:=\frac{\mathrm{7}}{\mathrm{2}} \\$$
Commented by Prithwish sen last updated on 01/Aug/19
$$\mathrm{Sir},\:\mathrm{you}\:\mathrm{have}\:\mathrm{to}\:\mathrm{change}\:\mathrm{the}\:\mathrm{limit}\:\mathrm{for}\:\boldsymbol{\mathrm{z}}. \\$$